2015
DOI: 10.1088/0957-4484/26/44/445603
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of homogenous multilayered W films by multi-step sputtering deposition: a novel grain boundary enrichment strategy

Abstract: Using a multi-step deposition approach, we develop a strategy of homogeneous multilayered (HM) structure to enrich the grain boundary (GB) of sputtered W films. In comparison with the single-layered film, the HM W film is easily controllable for the film GB density. When decreasing the film modulation period t m from 160 nm to 7 nm, the GB density gradually increased from 0.065 nm(-1) to 0.275 nm(-1) without changing the phase structure of the films. Accordingly, the film's electrical resistivity and mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…This is consistent with the results in some papers that the surface roughness of the deposited films increases with film thickness [54,55]. Zhu et al [53] also reported that this phenomenon was related to the variation in the grain size because RMS roughness was determined by the height fluctuations in the surface profiles.…”
Section: Effects Of Different Film Thicknesses On the Surface Roughne...supporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the results in some papers that the surface roughness of the deposited films increases with film thickness [54,55]. Zhu et al [53] also reported that this phenomenon was related to the variation in the grain size because RMS roughness was determined by the height fluctuations in the surface profiles.…”
Section: Effects Of Different Film Thicknesses On the Surface Roughne...supporting
confidence: 92%
“…Van Zwol et al [50] found that σ RMS of Au films increased from 1.68 to 9.92 nm when t film increased from 100 to 1600 nm. As well as Au, the surface roughness of titanium (Ti) [52] and tungsten (W) [53] has also been investigated by other researchers. Table 1 lists the deposition conditions and test results in detail.…”
Section: Effects Of Different Film Thicknesses On the Surface Roughne...mentioning
confidence: 99%